Genetic diversity and antibiotic resistance of Neisseria gonorrhoeae in Russia for the period 2022–2023 - Shagabieva Yu.Z.; Shpilevaya M.V.; Lagun K.M.; Ohlopkova O.V.; Plakhova K.I.; Nosov N.Yu. (Клиническая микробиология и антимикробная химиотерапия)
Objective.